Rhomboid-mediated cleavage of the immune receptor XA21 protects grain set and male fertility in rice - Satyam Vergish; Xiaoen Huang; Guiyun Zhang; Beatriz de Toledo Franceschi; Jian-Liang Li; Xiao-Xia Wu; Joana Nuraj; Jose C. Huguet-Tapia; Apekshya Parajuli; Xiuhua Chen; Ritu Shekhar; Dali Liu; et al. (Proceedings of the National Academy of Sciences, 2025)
To maintain growth and to successfully reproduce, organisms must protect key functions in specific tissues, particularly when countering pathogen invasion using internal defensive proteins that may disrupt their own developmental processes. The rice immune receptor XA21 confers race-specific resistance against Xanthomonas oryzae pv. oryzae , which causes the deadly disease bacterial leaf blight. Here, we demonstrate that XA21 is cleaved by the rhomboid-like protease OsRBL3b, likely within its transmembrane domain. OsRBL3b mRNA transcripts are preferentially expressed in rice spikelets. Rice plants expressing Xa21 but lacking a functional OsRBL3b displayed impaired anther dehiscence and pollen viability, resulting in male sterility and yield reduction with high levels of XA21 protein present in spikelets during anthesis. In leaves, osrbl3b mutants expressing XA21 had normal levels of this resistance protein and disease immunity. This balance between reproduction and disease resistance through the specific expression of a rhomboid protease may be key to limiting the detrimental effects of an active immune response and may be useful in future for genetic improvement of crops.